2017
DOI: 10.1088/1361-6579/aa552a
|View full text |Cite
|
Sign up to set email alerts
|

A non-invasive approach to investigation of ventricular blood pressure using cardiac sound features

Abstract: Heart sounds (HSs) are produced by the interaction of the heart valves, great vessels, and heart wall with blood flow. Previous researchers have demonstrated that blood pressure can be predicted by exploring the features of cardiac sounds. These features include the amplitude of the HSs, the ratio of the amplitude, the systolic time interval, and the spectrum of the HSs. A single feature or combinations of several features have been used for prediction of blood pressure with moderate accuracy. Experiments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The ECG parameters in this study were comparable with previously reported values in conscious healthy Beagles [49,50], while PCG parameters were similar to published reports in healthy dogs [51]. In the previous studies, it was reported that heart sound is correlated with the left ventricular systolic blood pressure and cardiac output [52,53]. The use of digital PCG allows a visual and measurable description of heart sounds and murmurs in dogs that can be valuable in disease diagnosis [51,[54][55][56].…”
Section: Discussionsupporting
confidence: 89%
“…The ECG parameters in this study were comparable with previously reported values in conscious healthy Beagles [49,50], while PCG parameters were similar to published reports in healthy dogs [51]. In the previous studies, it was reported that heart sound is correlated with the left ventricular systolic blood pressure and cardiac output [52,53]. The use of digital PCG allows a visual and measurable description of heart sounds and murmurs in dogs that can be valuable in disease diagnosis [51,[54][55][56].…”
Section: Discussionsupporting
confidence: 89%
“…Herein, we want to demonstrate that our soft EMAC sensing tattoo is capable of continuous BP estimation. So far, quite a few papers have mentioned the correlation between the STI and BP . Tang and co‐workers have noticed a strong negative correlation between systolic blood pressure (SBP) and systole through measurements on six subjects using a conventional ECG sensor and a microphone for PCG.…”
Section: Resultsmentioning
confidence: 99%
“…They stated that exercise elevated the heart rate and cardiac muscle contractility in the first phase, which would result in shorter valve closure time intervals . In later work, they conducted animal experiments to investigate the correlation between the systole (RAC) and the blood pressure of the left ventricle (LVBP) . The variation of BP, which ranged from 90 to 282 mmHg, controlled by different doses of epinephrine, was measured by an invasive catheter inserted into the left ventricle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, heart sound analysis is an important means of non-invasive detection of cardiovascular disease. It has become one of the effective methods for clinical diagnosis of the cardiac disease [1].…”
Section: Introductionmentioning
confidence: 99%